Bilateral anterior and intermediate uveitis in SARS-CoV-2 associated multisystem inflammatory syndrome in a pediatric patient - Jessica Shantha; Amit K. Reddy; Amol Sura; Adrian Tsang; Kareem Moussa; Nisha Acharya; John Gonzales; Thuy Doan (BMC, 2022)
Abstract Purpose To report a case of bilateral anterior intermediate uveitis after recovery from SARS-CoV-2 associated multisystem inflammatory syndrome in children (MIS-C). Case Report A 9-year-old male presented with bilateral anterior intermediate uveitis with fluorescein angiography (FA) leakage of the disc and peripheral vasculature 1 month after recovery from MIS-C. He was treated with difluprednate 0.05% in both eyes with resolution of FA leakage, but our patient has required an extended treatment of topical therapy and the need long term immunosuppression. Conclusions This is a case of uveitis presenting after recent MIS-C related to SARS-CoV-2. Ongoing follow up and monitoring is required, and it is important for the ophthalmologist and rheumatologist to be aware of this rare complication during the current COVID-19 pandemic.